Multiplex detection of pancreatic cancer biomarkers using a SERS-based immunoassay. (16th October 2017) - Banaei, Nariman; Foley, Anne; Houghton, Jean Marie; Sun, Yubing; Kim, Byung
Abstract: Early diagnosis of pancreatic cancer (PC) is critical to reduce the mortality rate of this disease. Current biological analysis approaches cannot robustly detect several low abundance PC biomarkers in sera, limiting the clinical application of these biomarkers. Enzyme linked immunosorbent assay and radioimmunoassay are two common platforms for detection of biomarkers; however, they suffer from some limitation. This study demonstrates a novel system for multiplex detection of pancreatic biomarkers CA19-9, MMP7 and MUC4 in sera samples with high sensitivity using surface enhanced Raman spectroscopy. Measuring the levels of these biomarkers in PC patients, pancreatitis patients, and healthy individuals reveals the unique expression pattern of these markers in PC patients, suggesting the great potential of using this approach for early diagnostics of PCs.